Cestovní ruch a ochrana přírody na Neziderském jezeře porovnání rakouského a maďarského přístupu - Šilhánková, Vladimíra; Pondělíček, Michael (Univerzita Pardubice, 2013)
The paper is focused on description and comparison of attitude on the edge between nature protection and tourism development in the area of former “iron curtain” between Austria and Hungary – at the Nesider Lake. The paper assesses nature protection system in the UNESCO and NATURE 2000 area as well as condition for tourism development on the both part of the border and compare them. Important source for paper preparation are direct observation in the Nesider Lake territory of authors and students of Regional Development studies realized during terrain excursion in the term from 15th till 20th April 2012.
Tourism and nature protection in the area of Nesider Lake Austrian and Hungarian comparison
Keywords: regional development; tourism; Nesider Lake; Austria; Hungary